2015
DOI: 10.1089/apc.2014.0255
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Antiretroviral Therapy Adherence and Plasma HIV RNA Suppression Among AIDS Clinical Trials Group Study Participants

Abstract: We conducted a secondary data analysis of 11 AIDS Clinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…Whereas adherence barriers like fear of side effects, pill burden, perceptions that ART is harmful, feeling sick and depressed have been associated with virologic detectability in various AIDS Clinical Trial Participants in United States, current first-line cART comprises low pill burden and improved safety profile with low toxicity [24]. Even if about 89% of women were receiving Efavirenz or Neviparine based regimen, ART regimen type was not significantly associated with virologic detectability.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas adherence barriers like fear of side effects, pill burden, perceptions that ART is harmful, feeling sick and depressed have been associated with virologic detectability in various AIDS Clinical Trial Participants in United States, current first-line cART comprises low pill burden and improved safety profile with low toxicity [24]. Even if about 89% of women were receiving Efavirenz or Neviparine based regimen, ART regimen type was not significantly associated with virologic detectability.…”
Section: Discussionmentioning
confidence: 96%
“…The link between these conditions has been established, 3941 but the level of impact is not immutable. Interventions to treat clinical depression and simultaneously support adherence with cognitive and behavioral skills can improve both depression and adherence outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to treat clinical depression and simultaneously support adherence with cognitive and behavioral skills can improve both depression and adherence outcomes. 41 Among patients with opioid dependence, methadone and buprenorphine maintenance can improve medication adherence, and directly administered ART has been associated with improved clinical outcomes among substance abusers. 42 …”
Section: Discussionmentioning
confidence: 99%
“…50 Qualitative studies have identified a number of patient-reported barriers to adherence, including forgetfulness, limited understanding of the importance of treatment, drug side effects, pill burden, disruptions to daily routine, and competing priorities. 51 Some studies have reported that feeling sick is a more frequent barrier to adherence than feeling healthy 52 ; this may in part be related to the higher pill burden associated with the treatment of comorbodities. 53 The relationship between baseline CD4 count and adherence to ART is complex and contextual, and other factors are likely as important or more important in determining adherence, as suggested by the variability in adherence levels between studies included in this review.…”
Section: Discussionmentioning
confidence: 99%